Housing in East Asia : socioeconomic and demographic challenges - Doling, John; Ronald, Richard (Palgrave Macmillan, 2020)
Housing policy has been central to the economic success stories of the major East Asian economies as well as a pillar of social and welfare provision. This book explores not only the development of their distinctive approach, but also the challenges posed in recent years, and currently, by rapid socio-economic and demographic change.